Segurista - Aquiluz, Tikoy; Lacaba, Jose F.; Lacueta, Amado, Jr; Dalawis, Jun; Cuatico, Eric; Del Rosario, Vic, Jr; Aldana, Michelle; Estrada, Gary; Martinez, Albert; Diaz, Julio (Viva Home Entertainment, 1996)
Karen works as an insurance saleswoman in Manila in the daytime but a club ecort in the night. She sells insurance to her escort clients in exchange of sexual favors. She saves money to buy a house and start a small business for her family who were a victim of Mount Pinatubo eruption. She met Sonny, a married rich car dealer, who offered her to live with him. After the incident with Ruby's boyfriend, she went to Pampanga riding a taxi. The taxi driver raped, killed and dumped her in a lahar area. During her funeral, Ruby gave Karen's gift to her daughter and the one million insurance certificate to her family.